A short report on Dengue Fever - Mahwish Fatima; Subia Jamil (Journal of Bahria University Medical and Dental College)
Dear Sir Dengue fever is a deadly mosquito-borne viral infection. It is caused by the bite of female mosquito by Aedes aegypti and in some cases also by Aedes albopictus, infected with the virus. Dengue virus is RNA virus, which is single-stranded. There are 4 types of viruses that cause dengue, named DEN-1, DEN-2, DEN-3, and DEN-4. Yet not all four types are found in particular region like Indian sub-continent is mainly restricted by the type 2 and 3. It has been documented that the Pakistan, Sri Lanka, India and Bangladesh are among those countries that are severely affected by the Dengue. In Pakistan, dengue is considered now one of the major health burdens with numerous incidences of complicated cases.1,2